Pure iron and nickel for new structural reactor materials - Pylypenko, M.M.; Stadnik, Yu.S.; Drobyshevska, A.O. (Вопросы атомной науки и техники, 2019)
The refining processes of iron and nickel from metal and gas impurities by physical methods in vacuum are considered. The effectiveness of using electron-beam melting for purification of these metals is shown. Iron and nickel in a purity of more than 99.98 and 99.994 wt.% respectively have been produced.